2018
DOI: 10.1186/s13012-018-0795-9
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: a cluster-randomized trial implementing Sustained Patient-centered Alcohol-related Care (SPARC trial)

Abstract: BackgroundExperts recommend that alcohol-related care be integrated into primary care (PC) to improve prevention and treatment of unhealthy alcohol use. However, few healthcare systems offer such integrated care. To address this gap, implementation researchers and clinical leaders at Kaiser Permanente Washington (KPWA) partnered to design a high-quality program of evidence-based care for unhealthy alcohol use: the Sustained Patient-centered Alcohol-related Care (SPARC) program. SPARC implements systems of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 79 publications
0
67
0
Order By: Relevance
“…Thus, our finding that homelessness was positively associated with treatment initiation for AUD is likely not generalizable. Several studies are testing whether integrating AUD treatment into primary care can overcome barriers to AUD treatment . Integrated care has been successfully trialed for patients with mental health and SUDs attending HCV clinics and has been shown to increase rates of HCV treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our finding that homelessness was positively associated with treatment initiation for AUD is likely not generalizable. Several studies are testing whether integrating AUD treatment into primary care can overcome barriers to AUD treatment . Integrated care has been successfully trialed for patients with mental health and SUDs attending HCV clinics and has been shown to increase rates of HCV treatment .…”
Section: Discussionmentioning
confidence: 99%
“…While the framework considered in this paper prioritized selecting a population using pre-randomization data for the primary analysis, other studies have taken alternate approaches [17]. One example is a pragmatic, open-cohort, stepped-wedge trial to evaluate a program integrating alcohol-related care into primary care [40]. A main objective of that prior trial was to test whether the intervention increased treatment for alcohol use disorders documented in the EHR as compared to usual primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding identification bias by restricting the analysis to patients diagnosed before randomization was not appealing because of the nature of the stepped wedge design, whereby patients seen in the clinic before randomization may not have follow-up visits to the clinic during the time period after the clinic crossed over to the intervention group (up to 2-3 years later). Consequently, investigators favored a primary analysis approach that used as its study population all patients who visited the clinic (including patients with a first visit after randomization), because the intervention was not expected to affect this population [40,46,47]. Another example is a cluster-randomized, parallel group trial to test the effectiveness of an intervention to improve colorectal cancer screening rates [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of practice facilitation in primary care settings; a meta-analysis found that odds of providing evidence-based preventive care were 2.76 times higher (95% CI 2.18–3.43) in primary care settings with practice facilitation [ 30 ]. Practice facilitation is increasingly being tested as a means of increasing the provision of substance use-related care in diverse clinical settings [ 34 ], including alcohol-related care in primary care clinics [ 35 ]. However, to our knowledge, the use of practice facilitation to implement alcohol-related care in liver clinic settings has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%